OPTIMALISASI PERAN PERPUSTAKAAN DESA DALAM MENUMBUHKAN BUDAYA LITERASI MELALUI LOMBA MEMBACA NYARING PADA SISWA SD/MI DI DESA SAWOCANGKRING, SIDOARJO - Amima Na’ma; Fathul Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literacy activities play an important role in improving the quality of education, especially at the elementary level. The low reading interest among elementary school students encourages the need for creative and participatory strategies to foster a literacy culture. This study aims to analyze the optimization of the role of the Sawocangkring Village Library in developing a literacy culture through loud reading competitions for SD/MI students in Sawocangkring Village, Sidoarjo. The method used is a descriptive qualitative approach through observation, interviews, and documentation. The village library acts as a facilitator of activities by providing facilities, reading materials, and coordinating with schools and the village government in implementing the literacy program. The results of the study show that optimizing the role of the village library through loud reading competitions can increase reading interest, comprehension of reading materials, public speaking skills, and students’ self-confidence. Therefore, Thus, the village library can serve as a center for community literacy development, while the loud reading competition becomes one of the effective strategies in fostering a literacy culture among elementary school students.